Modern Chinese Counter-Enlightenment Affect, Reason, and the Transcultural Lexicon. - Peng, Hsiao-yen (Hong Kong University Press, 2023)
In Modern Chinese Counter-Enlightenment: Affect, Reason, and the Transcultural Lexicon, Peng Hsiao-yen argues that a trend of Counter-Enlightenment had grown from the late Qing to the May Fourth era in the 1910s to the 1920s and continued to the 1940s. She demonstrates how Counter-Enlightenment was manifested with case studies such as Lu Xun's writings in the late 1900s, the Aesthetic Education movement from the 1910s to 1920s, and the Science and Lifeview deb.